Design and expression of a chimeric recombinant antigen (SsIR-Ss1a) for the serodiagnosis of human strongyloidiasis: Evaluation of performance, sensitivity, and specificity. - Mostafa Omidian; Zohreh Mostafavi-Pour; Marzieh Asadi; Meysam Sharifdini; Navid Nezafat; Ali Pouryousef; Amir Savardashtaki; Mortaza Taheri-Anganeh; Fattaneh Mikaeili; Bahador Sarkari (PLoS Neglected Tropical Diseases)
Background The sensitivity of parasitological and molecular methods is unsatisfactory for the diagnosis of strongyloidiasis, and serological techniques are remaining as the most effective diagnostic approach. The present study aimed to design and produce a chimeric recombinant antigen from Strongyloides stercoralis immunoreactive antigen (SsIR) and Ss1a antigens, using immune-informatics approaches, and evaluated its diagnostic performance in an ELISA system for the diagnosis of human strongyloidiasis. Methodology/principal findings The coding sequences for SsIR and Ss1a were selected from GenBank and were gene-optimized. Using bioinformatics analysis, the regions with the highest antigenicity that did not overlap with other parasite antigens were selected. The chimeric recombinant antigen SsIR- Ss1a, was constructed. The solubility and physicochemical properties of the designed construct were analyzed and its tertiary structures were built and evaluated. The construct was expressed into the pET-23a (+) expression vector and the optimized DNA sequences of SsIR-Ss1a (873 bp) were cloned into competent E. coli DH5α cells. Diagnostic performances of the produced recombinant antigen, along with a commercial kit were evaluated in an indirect ELISA system, using a panel of sera from strongyloidiasis patients and controls. The physicochemical and bioinformatics evaluations revealed that the designed chimeric construct is soluble, has a molecular with of 35 KDa, and is antigenic. Western blotting confirmed the immunoreactivity of the produced chimeric recombinant antigen with the sera of strongyloidiasis patients. The sensitivity and specificity of the indirect ELISA system, using the produced SsIR-Ss1a chimeric antigen, were found to be 93.94% (95% CI, 0.803 to 0.989) and 97.22% (95% CI, 0.921 to 0.992) respectively. Conclusions/significance The preliminary findings of this study suggest that the produced SsIR-Ss1a chimeric antigen shows promise in the diagnosis of human strongyloidiasis. However, these results are based on a limited panel of samples, and further research with a larger sample size is necessary to confirm its accuracy. The construct has potential as an antigen in the ELISA system for the serological diagnosis of this neglected parasitic infection, but additional validation is required.